Neocolpocephalum turbinatum lice in Pekin ducks (Anas platyrhynchos domesticus) in Artemisa province, Cuba - García Ferrer, Yenisey (2020)
The study aimed to determine the behaviour of ectoparasites in Pekin ducks (Anas platyrhychos domesticus) from the province of Artemisa, Cuba. Samples of 30 adult ducks of both sexes from various farms were analysed. For the sampling, three to five feathers were extracted from each corporal area (head, back, wings, cloaca area, tail, anterior thigh, pectoral area) and the indicators of invasion intensity and prevalence were determined. The collected parasites were mounted in Hoyer's solution and incubated at 28 °C for seven days for the clarification of the samples for their subsequent taxonomic identification. The specimens found correspond to the louse Neocolpocephalum turbinatum. This finding reveals that although the host of this insect is Columba livia, it can be found in other bird orders, due to gaps in biosecurity. The prevalence was 13.3% and the intensity was mild, which does not cause obvious damage. Neocolpocephalum turbinatum is reported to be present in Peking ducks as a new host in Cuba.